The Sorption of Cesium and Strontium Ions onto Red-Clay from Sivrihisar-Eskisehir (Turkey) - Bassari, Asiye; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Kluwer Academic Publishers, 2000)
The sorption of Cs and Sr ions fromaqueous solutions (concentration range: 20–400 mg/L)by red-clay from Sivrihisar-Eskisehir (Turkey) hasbeen investigated using EDXRF spectrometry. The XRDpattern of the sample indicates that it containsmontmorillonite, illite, albite, chlorite and quartz.The results indicate the presence of correlationsbetween sorbed Cs ions and desorbed Na and K ions andsorbed Sr ions and desorbed Mg and Ca ions. Sorptionprocesses are found to show a Freundlich-typebehaviour. The Dubinin–Radushkevich (D–R) isotherm hasbeen applied to the sorption data and the parametersof the D–R equation were calculated.
Keywords: cesium; strontium; clay; adsorption